CONSULTING AS A FACTOR OF PROFESSIONAL INTEGRATION: ANALYSIS OF THE ADAPTATION OF BEAUTY INDUSTRY SPECIALISTS WITH INTERNATIONAL EDUCATION TO U.S. REGULATORY REQUIREMENTS - Блажко, Катерина (SWorldJournal, 2026)
The article provides a comprehensive analysis of the role of specialized consulting in the process of professional integration of beauty industry specialists (hairdressing, nail services, aesthetics), as well as related licensed fields, particularly massa